Whole Genome Profiling of Lung Microbiome in Solid Organ Transplant Recipients Reveals Virus Involved Microecology May Worsen Prognosis - Pan, Lingai; Wu, Fengsheng; Cai, Qingqing; Xu, Zhuofei; Hu, Huan; Tang, Tian; Yue, Ruiming; Hou, Yifu; Zhang, Xiaoqin; Fang, Yuan; Huang, Xiaobo; Kang, Yan (Frontiers in Cellular and Infection Microbiology, 2022)
Solid organ transplantation (SOT) is the final therapeutic option for recipients with end-stage organ failure, and its long-term success is limited by infections and chronic allograft dysfunction. Viral infection in SOT recipients is considered an important factor affecting prognosis. In this study, we retrospectively analyzed 43 cases of respiratory infections in SOT recipients using metagenomic next-generation sequencing (mNGS) for bronchoalveolar lavage fluid (BALF). At least one virus was detected in 26 (60.5%) recipients, while 17 (39.5%) were virus-negative. Among virus-positive recipients, cytomegalovirus (CMV) was detected in 14 (32.6%), Torque teno virus (TTV) was detected in 9 (20.9%), and other viruses were detected in 6 (14.0%). Prognostic analysis showed that the mortality of the virus-positive group was higher than that of the virus-negative group regardless whether it is the main cause of infection. Analysis of different types of viruses showed that the mortality of the CMV-positive group was significantly higher than that of the CMV-negative group, but no significant difference was observed in other type of virus groups. The diversity analysis of the lung microbiome showed that there was a significant difference between the virus-positive group and the negative group, in particular, the significant differences in microorganisms such as Pneumocystis jirovecii (PJP) and Moraxella osloensiswere detected. Moreover, in the presence of CMV, Pneumocystis jirovecii, Veillonella parvula, and other species showed dramatic changes in the lung of SOT patients, implying that high degree of co-infection between CMV and Pneumocystis jirovecii may occur. Taken together, our study shows that the presence of virus is associated with worse prognosis and dramatically altered lung microbiota in SOT recipients.